2008
DOI: 10.1159/000127447
|View full text |Cite
|
Sign up to set email alerts
|

Unsuccessful Induction of Endometriosis in Female Rhesus Macaques <i>(Macaca mulatta)</i>

Abstract: Background/Aims: The aim of this study was to induce endometriosis in female rhesus macaques (Macaca mulatta) for research purposes. Methods: Three female monkeys from 4 to 4.5 years of age underwent three consecutive attempts at endometriosis induction over an 8-month period: (i) the first attempt involved intravaginal sampling of endometrial tissue and transplantation into the intrapelvic cavity; (ii) the second entailed surgical removal of endometrium after hysterotomy and intra-abdominal placement, and (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…This work validated a surgical protocol for creating endometriosis in rhesus macaques that recapitulates in part the outcome of retrograde menstruation. Earlier studies to develop a macaque model for induced endometriosis reported variable success 37,38 . Creating the disease in macaques via transcervical collection of menstrual endometrium is not feasible because the complex anatomy of the macaque cervix 42 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This work validated a surgical protocol for creating endometriosis in rhesus macaques that recapitulates in part the outcome of retrograde menstruation. Earlier studies to develop a macaque model for induced endometriosis reported variable success 37,38 . Creating the disease in macaques via transcervical collection of menstrual endometrium is not feasible because the complex anatomy of the macaque cervix 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies to develop a macaque model for induced endometriosis reported variable success. 37,38 Creating the disease in macaques via transcervical collection of menstrual endometrium is not feasible because the complex anatomy of the macaque cervix. 42 Our uterine puncture technique provides a "surgically sterile" approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations